Hereditary tumors: from genes to clinical consequences - Allgayer, Heike; Rehder, Helga; Fulda, Simone (Wiley-VCH, 2009)
Hereditary Tumors; Foreword; Preface; Contents; List of Contributors; Part I Hereditary Tumors -- General Aspects; 1 General Insights Into Tumor Invasion, Progression, and Metastasis; 2 The Genetic Background of Hereditary Tumor Diseases; Part II Syndromal Types of Hereditary Tumors; 3 Family Cancer Syndromes; 4 Genetic Dysmorphic Syndromes Leading to Tumorigenesis; Part III Site-Specific Aspects of Hereditary Tumors; 5 Hereditary Brain Tumors; 6 Neurofibromatosis; 7 Retinoblastoma: The Prototypic Hereditary Tumor; 8 Hereditary Cancer in the Head and Neck.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Erbkrankheit; Krebs